Assessing the Current Evidence on Singultus (Hiccups): Epidemiology, Pathophysiology, Differential Diagnosis, and Management - Maalini Raajaa; Satheeshkumar Palanivel; Kugalur Ganesan Parthiban; Sangameswaran Balakrishnan; Kalpana Devi Mahalingam; Thilagesh Ponnuvel; S Anand kumar; Aiswarya Nair U; Mohankumar Muniyappan (The Bioscan, 2025)
Hiccups are sudden involuntary contractions of the diaphragm that A variety of causes, such as factors like eating too quickly or too much, and drinking carbonated beverages can make someone hiccup. Stress is another known trigger, and there are certain medical conditions that can also lead to frequent hiccups. Symptoms of hiccups include repeated, sudden closure of the glottis, producing a characteristic sound. Most people don’t realize that a hiccup is really a spasm of the entire diaphragm (not just one half as in normal breathing), accompanied by one half of the brain working differently from the other. The record for the longest bout of hiccups is held by a man who hit up for 68 days back in Although hiccups are usually self-limiting and harmless, persistent or severe cases can disturb and disrupt daily life. Treatment options for hiccups range from simple home remedies, such as holding one’s breath or drinking water, to pharmacological interventions, including antacids and anxiolytic medications.